Al-Biruni’s Historical Method (973 M-1048 M) in Kitab Tarikh Al-Hind - Putri, Fira Dwi; Yasmin, Nabila (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Abu al-Rayḥan Muḥammad ibn Aḥmad al-Biruni (973 M – 1048 M) is known as a multidisciplinary scholar who applied direct observation, verification, and critical analysis in writing history. This research examines al-Biruni's contribution to Islamic historiography through an analysis of his monumental work, Kitab tarikh al-hind, which contains in-depth studies of religion, philosophy, culture, science, geography, and the social life of Indian society. The historical method used in this research consists of five main steps, namely topic selection, heuristics (collection of primary and secondary sources), source criticism, interpretation, and historical writing. This approach is combined with the descriptive-comparative method to describe and compare al-Biruni's historiography method with modern historiography standards. The results show that al-Biruni applied various auxiliary sciences such as social science, culture, astronomy, mathematics, and linguistics in building an accurate and objective historical reconstruction. The approach of combining written, oral, and field observation sources reflects the concept of data triangulation that is now standard in scientific research. As such, the Kitab tarikh al-hind relies not only on narrative tradition, but also empirical evidence, making it an excellent work of scholarly historiography that is relevant today.